Board Gender Diversity, Corporate Social Disclosures, and National Culture. (October 2022) - Peng, Xuhui; Qi, Tian; Wang, Gang
The impact of board gender diversity on corporate social responsibility has attracted considerable attention in recent years. However, the study of the relationship between board gender diversity, corporate social disclosures, and national culture has been scarce. Therefore, in this study, we measured the corporate social disclosures data of multinational corporations (MNCs) from China, Japan, the United Kingdom, and the United States using content analysis. Then, we investigated the relationship between board gender diversity and the corporate social disclosures of MNCs as well as the moderating effect of national culture on that relationship. The results show that (1) board gender diversity positively impacts the corporate social disclosures of MNCs and that (2) masculinity negatively moderates the relationship between board gender diversity and the corporate social disclosures of MNCs. The findings emphasize the importance of board gender diversity in the stakeholder management of the board of directors and how it could be affected by different national cultural environments from the stakeholder theory perspective. This study established a link between board gender diversity, corporate social disclosures, and national culture as well as promoted the development of corporate social responsibility (CSR) disclosure measurement methods. Additionally, our results provide suggestions to policymakers and MNCs in how to effectively adopt board gender diversity to promote CSR in specific national cultural environments.